Problems of Occupational Injuries and Ways of Its Reduction on Example of Ukraine - Mezentseva, Iryna; Kuzmenko, Olena; Osmanova, Olga; Vambol, Sergij (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Manuscript presents a study of the causes of accidents on the example of Ukraine in recent years, considering the peculiarities of the modern period. The relevance of this study is due to the high level of industrial injuries in Ukraine compared to the industrialized countries of the European Union. Data on the dynamics of the causes of accidents for the period from 2015 to 2022 are presented. Data for the study were taken from open sources of information. The most trauma-dangerous industries of the national economy are considered. Proposed measures to reduce the level of injury in Ukraine. The analysis of the obtained results showed a certain dependence of the causes of accidents on the coronavirus infection. An unchanging leading position in the organizational causes of accidents has been established. According to the results of the study, regularities were established regarding the most traumatic sectors of the economy in the presented years. The predominance of organizational causes of industrial injuries due to the low motivational component of occupational safety is shown. The need to improve training on occupational health and safety issues for employees at all levels was noted. It was established that the reduction of industrial injuries is impossible without the teaching of labor protection issues in institutions of higher education by future heads of structural divisions and leading specialists. Mandatory review and re-approval of the instructions, the violation of which led to an accident, is proposed. It is recommended to apply mandatory professional selection and more thorough control over periodic preventive medical examinations.